Longitudinal photo-documentation:: Recording living walls - Hansen, Susan; Flynn, Danny (SAUC - Street Art and Urban Creativity (repository), 2015)
This working paper advocates a methodological approach to the study of street art and graffiti that is based on the documentation of single sites over time. Longitudinal photo-documentation is a form of data collection that allows street art and graffiti to be examined as visual dialogue. By capturing everyday forms of public mark making alongside both more recognizably ‘artistic’ images, and more visually ‘offensive’ tags, we aim to attend to graffiti and street art’s existence within a field of social interaction. We describe a relevant analytic tool drawn from ethnomethodology and conversation analysis – the next turn proof procedure – which may be adapted in order to study street art and graffiti as a form of asynchronous, yet sequential, communication. This form of analysis departs from existent forms of analysis in that it is not concerned with the semiotics or iconography of decontextualized individual photographs of street art or graffiti. We present a worked analytic example to demonstrate the utility of longitudinal photo-documentation in making visible the dialogue amongst artists, writers and community members, and we employ the principles of the next turn proof procedure to illustrate the ways in which each party shows their understanding of the prior work on the wall via their own contribution to the ‘conversation.’